Brief overview of effervescent atomizer application. (August 2019) - Zhao, Fang; Ren, Zebin; Xu, Bingbing; Zhang, Haiyang; Fu, Cheng
Abstract: Effervescent atomizer is a kind of atomizer which uses bubbles as power of atomizing, and realizes atomization process through bubble formation, movement, deformation, as well as exit blasting. Compared with conventional pressure atomizer and pneumatic atomizer, it has the advantages of high efficiency, economy and environmental protection, thus attracting attention from all walks of life. Applications of effervescent atomizer in gas turbine combustor, internal-combustion engine, furnace and boiler and other fields were briefly viewed through classification and summary of large quantities of literature at home and abroad. Technical difficulties and development prospects of effervescent atomizer in the application research process were briefly analysed, and related research results were given, which providing reference for design and application of effervescent atomizer.